THE USE OF TURMERIC (Curcuma longa) EXTRACT AS A NATURAL COLORANT IN SMART PACKAGING TO DETECT QUALITY DETERIORATION OF FRESH WHOLE VANNAMEI SHRIMP (Litopenaeus vannamei) - Kevin Kusuma; Iis Rostini; Ayi Yustiati; Emma Rochima (Universitas Mataram, 2026)
This study aimed to determine the optimal concentration of yellow turmeric (Curcuma longa) extract incorporated into smart packaging capable of detecting quality deterioration of Vannamei shrimp through indicator label color changes in response to variations in pH and Total Volatile Base (TVB) values, as well as providing timely information regarding the freshness of the packaged fresh Vannamei shrimp. The study was designed using a Completely Randomized Design (CRD) with an experimental method consisting of four treatments, namely the addition of yellow turmeric extract at concentrations of 0%, 1%, 2%, and 3%, with ten replications. The treatments were subsequently applied in the packaging of Vannamei shrimp stored for 6 days at a temperature of 10°C. Observation parameters included the characteristics of color changes of the indicator label during storage and their relationship with the organoleptic characteristics of shrimp freshness, including appearance, odor, and texture, as well as measurements of pH and TVB values during storage. Organoleptic test data were analyzed using the Kruskal–Wallis test, and when significant differences were observed, a multiple comparison test was conducted. Data on color changes, pH, and TVB values were analyzed descriptively. The results demonstrated that the use of smart packaging for Vannamei shrimp with indicator labels incorporated with yellow turmeric extract and stored for 6 days showed that the addition of 2% yellow turmeric extract was the best treatment. The 2% turmeric extract effectively detected quality deterioration of Vannamei shrimp based on clear gradations of indicator label color changes during storage and in terms of timeliness with respect to shrimp quality deterioration. The indicator label color changed from bright yellow to yellowish-brown along with the decline in shrimp freshness, accompanied by increases in pH and TVB values during storage at 10°C.